Genetic data of 10 X-chromosomal loci in Vitória population (Espírito Santo State, Brazil) - Martins, J. A. [UNESP]; Costa, J. C. [UNESP]; Paneto, G. G. [UNESP]; Gusmão, L.; Sánchez-Diz, P.; Carracedo, A.; Cicarelli, Regina Maria Barretto [UNESP] (Elsevier, 2009)
Genetic population data for 10 X-STR (DXS8378, DXS9898, DXS7133, GATA31E08, GATA172D05, DXS7423, DXS6809, DXS7132, DXS9902 and DXS6789) were obtained from Vitória population (Espírito Santo State, Brazil). No deviations from the Hardy-Weinberg equilibrium and linkage disequilibrium were observed. The combined powers of discrimination in males and females were 0.9999995 and 0.99999999996, respectively. These high values show the potential of this system in human identification in Vitória population, Brazil. © 2009 Elsevier B.V. All rights reserved.
Keywords: Brazil; Genetic population data; Human identification; Vitória; X-STR; genomic DNA; female; gene frequency; gene linkage disequilibrium; gene locus; genetic database; genetic identification; haplotype; human; male; normal human; parentage analysis; population differentiation; population genetic parameters; priority journal; sexism; short tandem repeat; X chromosome